Inheritance of leaf characteristics in rice (Oryza sativa L.) - Masuduzzaman, ASM; Islam, MD Rafiqul; Alim, MA; Khatun, H; Hossain, MK (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 35-38